Effects of square-stepping exercise on cognitive functions of older people - Teixeira, Camila Vieira Ligo [UNESP]; Gobbi, Sebastião [UNESP]; Pereira, Jessica Rodrigues [UNESP]; Vital, Thays Martins [UNESP]; Hernandéz, Salma Stéphany Soleman [UNESP]; Shigematsu, Ryosuke; Gobbi, Lilian Teresa Bucken [UNESP] (Wiley, 2013)
Aim: Cognitive functions can decline with age, and interventions focusing on stimulating them may have positive results. Previous studies have shown that square-stepping exercise (SSE) has a good influence on balance, but this exercise also seems to promote cognitive stimulation. Therefore, the purpose of the present study was to analyse the effect of 16 weeks of SSE on cognitive functions in non-demented community-dwelling older people. Methods: This was a longitudinal, non-randomized study. Forty-one older adults (60 years and older) were recruited, and 21 participated in the SSE group (practised only SSE sequences) and 20 were in the control group (continued with their activities of daily living). Both groups were evaluated using the Mini-Mental State Examination, the Digit Span test, the Toulouse-Pierón Attention Test and the Modified Card Sorting Test. Results: The SSE group showed a significant improvement in global cognitive status, concentrated attention and mental flexibility after 16 weeks of the SSE intervention. Conclusion: Evidence shows that SSE is a physical activity that positively influences cognitive functions in non-demented older people. © 2013 Japanese Psychogeriatric Society.
Keywords: Cognitive functions; Elderly; Square-stepping exercise